Amartya Sen y el estudio de la desigualdad económica y la pobreza monetaria. Colombia: 1978-1997 The contributions of Amartya Sen to the study of inequality and poverty. Colombia 1978-1997 - Aguilar Ana; Nina B Esteban (Cuadernos de Economía, 1998)
Este artículo presenta el Índice de Pobreza y desigualdad de Amartya Sen, la familia de indicadores de Foster-Greer-Thorbecke y la forma en que se pueden utilizar uno y otra para determinar la magnitud de la pobreza y desigualdad en Colombia. Propone, además, que estos indicadores se utilicen para evaluar el incremento o la disminución de la desigualdad y la pobreza y para ajustar permanentemente las políticas económicas y sociales. This article presents Arnartya Sen's poverty and inequality index and the family of Foster-Greer-Thorbecke indicators, and the way in which they can be used to determine the magnitude of poverty and inequality in Colombia. In addition, it proposes that these indicators be used to evaluate the impact of social and economic policies on the poor population, to measure the increase or decrease in inequality and poverty, and to permanently adjust economic and social policies.